"I make my students' assignments bleed with red circles": An autoethnography of translanguaging in higher education in Pakistan. (March 2022) - Syed, Hassan
Abstract: In this paper, I discuss the tension between official monoglossic language ideologies and the heteroglossic classroom realities in higher education in Pakistan. Pakistan has maintained an English as the only medium-of-instruction policy in higher education since independence in 1947, while the everyday classroom practices have been characterized by translanguaging, that is, a hybrid and fluid use of plurilingual resources for communication. Using an autoethnographic lens, I discuss the intuitional processes and discursive practices within which my own experiences with deficit ideologies were shaped as an English language teacher and as I journied into translanguaging. Based on my experiences, I argue that while translanguaging shows great promise to confront monoglossic language ideologies inside the classroom, it offers fewer tools to resist unjust linguistic and social structures.